2013
DOI: 10.1016/j.fuel.2012.12.073
|View full text |Cite
|
Sign up to set email alerts
|

Neural network modeling of SBS modified bitumen produced with different methods

Abstract: h i g h l i g h t s " Mixing polymers into bitumen has important consequences on the engineering properties. " Structural changes may be observed during processing of polymer-modified bitumens. " Complex modulus determination of PMBs is important to select the performance grade. " With the increase of experimental factors experimental trials increases exponentially. " Complex modulus predicted accurately with the developed ANN model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The importance is constructing a new structure of an information processing system. ANN operates together through a great deal of highly interconnected processing neurons to work out issues [ 1 ].…”
Section: Artificial Neural Network (Anns)mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance is constructing a new structure of an information processing system. ANN operates together through a great deal of highly interconnected processing neurons to work out issues [ 1 ].…”
Section: Artificial Neural Network (Anns)mentioning
confidence: 99%
“…With the dramatic increase in modern road traffic flow, frequency and axle weight of vehicles, more rigorous requirements have been placed on the performance and durability of pavement materials. Over decades of research, it has been found that polymer modifiers can effectively improve the performance of asphalt and enhance the durability of road materials [ 1 , 2 , 3 , 4 ]. Of which, SBS modifiers in particular are the best [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on several past researches, the base bitumen and the polymer are heated at such temperature to ensure that the base bitumen and polymer are above their softening points. Also, it is necessary to heat the bitumen at high temperatures to allow the polymer particles to become soluble during production [29][30][31][32]. The SBS was then added gradually to the base bitumen and the rotating speed was kept at 2000 rpm for 1 hour.…”
Section: Preparation Of Modified Bitumen Samplesmentioning
confidence: 99%
“…Yapay zeka yöntemleri arasında hızlı sonuç alma, kullanım kolaylığı gibi sebeplerden dolayı Yapay Sinir Ağları (YSA) çokça tercih edilmektedir. Kök ve ekibi yaptıkları çalışmada YSA kullanarak farklı şartlarda Stiren -Butadien -Stiren (SBS) ile modifiye edilmiş bitümlü bağlayıcıların kompleks modül değerlerini yüksek doğrulukla elde etmişlerdir [32]. Özşahin ve Oruç, yapay sinir ağlarını kullanarak emülsifiye bitümün esneklik modülünü deneysel verilerle yüksek benzerlik elde ederek tahmin etmiştir.…”
Section: Introductionunclassified